2015
DOI: 10.1200/jco.2014.55.8627
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial Comparing Weekly Docetaxel Plus Cisplatin Versus Docetaxel Monotherapy Every 3 Weeks in Elderly Patients With Advanced Non–Small-Cell Lung Cancer: The Intergroup Trial JCOG0803/WJOG4307L

Abstract: This study failed to demonstrate any survival advantage of weekly docetaxel plus cisplatin over docetaxel monotherapy as first-line chemotherapy for advanced NSCLC in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 21 publications
3
79
1
Order By: Relevance
“…Single agents, including docetaxel or vinorelbine, have been recommended for the treatment of elderly patients with advanced NSCLC. In Japan, the results of phase III trials reported by Kudoh et al (22) and Abe et al (5) indicated that docetaxel was suitable for such patients. Kudoh et al (22) reported the OS, PFS and ORR of docetaxel were 14.3 months, 5.5 months and 22.7%, respectively.…”
Section: Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Single agents, including docetaxel or vinorelbine, have been recommended for the treatment of elderly patients with advanced NSCLC. In Japan, the results of phase III trials reported by Kudoh et al (22) and Abe et al (5) indicated that docetaxel was suitable for such patients. Kudoh et al (22) reported the OS, PFS and ORR of docetaxel were 14.3 months, 5.5 months and 22.7%, respectively.…”
Section: Responsementioning
confidence: 99%
“…The incidence of lung cancer has been increasing among elderly individuals, and single agents including vinorelbine and docetaxel have been widely used as first-line treatments against NSCLC in elderly patients with advanced disease in Japan. In a phase III study, Abe et al (5) reported that the survival time following docetaxel monotherapy was significantly increased compared with combination therapy with docetaxel plus cisplatin in elderly patients with advanced NSCLC. Therefore, it remains unclear whether combination chemotherapy improves survival compared with monotherapy in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no positive trial of platinum doublets chemotherapy has been verified for elderly Japanese patients with advanced NSCLC, as was recently demonstrated by the Japanese cohort (JCOG0803/ WJOG4307L trial) study which was terminated earlier than planned in the interim analysis [12]. Thus, the standard of care for such patients remains as docetaxel singlet chemotherapy at a dose of 60 mg/m 2 , which is based on the recommended dose for a Japanese cohort [13].…”
Section: Discussionmentioning
confidence: 93%
“…Both combinations demonstrated to be safe. Better results in terms of ORR and MST were demonstrated by Ohe et al [42] in patients aged ≥ 75 years by adding docetaxel to weekly cisplatin [42,43] . In 2007 Gridelli et al [44] tested in the MILES 2P the feasibility of cisplatin with gemcitabine or vinorelbine in elderly patients.…”
Section: Platinum-based Chemotherapy: Prospectives Studiesmentioning
confidence: 95%